2021
DOI: 10.2166/wh.2021.133
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 in wastewater is influenced by sampling time, concentration method, and target analyzed

Abstract: The detection of SARS-CoV in wastewater has been proposed as a tool for monitoring COVID-19 at the community level. Although many reports have been published about detecting viral RNA in wastewater and its presence has been linked to infected people, appropriate analytical methodologies to use this approach have not yet been established. In this study, we compared ultrafiltration, polyethylene glycol precipitation, flocculation using AlCl3, and flocculation with skim milk for the recovery of SARS-CoV-2, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…However, the combination of different control viruses and methods used by other groups, makes difficult to compare recovery efficiencies. The data got in this study showed low recovery and a great variability for both methods, 8.37% ± 5.88 n = 43 (method 4); 6.97% ± 6.51 n = 20 (method 5), in comparison with other data found in the bibliography relating to other control viruses, such as 1.6–2.6% for Murine Norovirus, 26.7–64.7% for MHV, 73 ± 50% for F-specific RNA, 42% and 30% for Pseudomonas phage φ6 20 , 27 , 36 . Even when results using the same control virus and method were compared, such as virus recovery showed in this work using method 5 (6.97% ± 6.51), data from Randazzo et al 26 (10% ± 2.1%) and data from Pérez-Cataluña et al 38 (9.0 ± 2.2%), there are other factors which could affect the results, such as the type of sample or the kits used for the RNA extraction and the RT-qPCR quantification.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, the combination of different control viruses and methods used by other groups, makes difficult to compare recovery efficiencies. The data got in this study showed low recovery and a great variability for both methods, 8.37% ± 5.88 n = 43 (method 4); 6.97% ± 6.51 n = 20 (method 5), in comparison with other data found in the bibliography relating to other control viruses, such as 1.6–2.6% for Murine Norovirus, 26.7–64.7% for MHV, 73 ± 50% for F-specific RNA, 42% and 30% for Pseudomonas phage φ6 20 , 27 , 36 . Even when results using the same control virus and method were compared, such as virus recovery showed in this work using method 5 (6.97% ± 6.51), data from Randazzo et al 26 (10% ± 2.1%) and data from Pérez-Cataluña et al 38 (9.0 ± 2.2%), there are other factors which could affect the results, such as the type of sample or the kits used for the RNA extraction and the RT-qPCR quantification.…”
Section: Discussionsupporting
confidence: 65%
“…The presence of organic matter limits the volume to be load, because could cause the filters to collapse. Indeed, Pino et al 36 showed differences in virus recovery using wastewater and deionized water, suggesting a negative effect of the presence of pollutants in wastewater analysis. Other studies have demonstrated that the removal of the solid can reduce the virus recovery, since the virus is retained in the pellet 33 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PEG-precipitation presented higher recovery efficiency than AlCl 3 flocculation ( Perez-Cataluna et al, 2021 ), and skimmed milk flocculation ( Pino et al, 2021 ) in other studies comparing virus concentration methods. However, this result disagrees with our previous study, which found that AlCl 3 flocculation outperformed PEG-precipitation using SARS-CoV-2 spiked wastewater for method evaluation ( Zheng et al, 2022a ).…”
Section: Resultsmentioning
confidence: 82%
“…Despite the simple concept of WBE, producing high-quality, accurate and reproducible data is challenging and quality issues can at any stage of the process. Sample collection- and processing-related quality issues, however, are not the focus of this study and are reviewed in detail by Polo et al, ( 2020 ), Pino et al, ( 2021 ) and Ahmed et al, ( 2022 ). The challenges of producing high-quality WBE data, however, continue beyond quantification of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%